Interoception and respiratory sinus arrhythmia in gambling disorder. (21st January 2019) - Kennedy, Dawn; Goshko, Caylee‐Britt; Murch, W. Spencer; Limbrick‐Oldfield, Eve H.; Dunn, Barnaby D.; Clark, Luke
Abstract: Gambling has longstanding links with excitement and physiological arousal, but prior research has not considered (a) gamblers' ability to detect internal physiological signals, or (b) markers of parasympathetic functioning. The present study measured interoception in individuals with gambling disorder, using self‐report measures and a heartbeat counting task administered at rest. Resting state respiratory sinus arrhythmia (RSA), an index of heart rate variability, was measured as a proxy for parasympathetic control and emotional regulation capacity. In a case‐control design, 50 individuals with gambling disorder were compared against 35 controls without gambling problems. Participants completed two self‐report measures of bodily awareness and a behavioral test of heartbeat counting. A resting state electrocardiogram (5 min) was used to calculate RSA. There were no significant differences on the self‐report or behavioral interoception probes. The group with gambling disorder displayed significantly reduced RSA, which at face value is consistent with reduced parasympathetic control. However, the group difference in RSA did not survive controlling for age and smoking status, as established predictors of heart rate variability. Our findings do not support any changes in interoceptive processing in people with gambling disorder, at least under resting conditions. Our observation that group differences in RSA are partly explained by smoking behavior highlights the importance of controlling for nicotine use in future research characterizing physiological functioning and emotional regulation in disordered gambling. Abstract : Gambling behavior has longstanding links with physiological arousal. This study compared individuals with gambling disorder and a healthy control group in interoception (i.e., the ability to detect physiological signals) and on resting‐state respiratory sinus arrhythmia (RSA), a marker of parasympathetic function. The groups did not differ significantly across multiple measures of interoception, and a group difference in RSA was driven by individual differences in age and smoking. Our findings provide novel context to theories that emphasize physiological arousal as a reinforcer of gambling behavior and highlight the importance of controlling for smoking behavior in physiological studies of gambling.